Encapsulation of purple basil leaf extract by electrospraying in double emulsion (W/O/W) filled alginate-carrageenan beads to improve the bioaccessibility of anthocyanins - Ozcan, Basak Ebru; Saroglu, Oznur; Karakas, Canan Yagmur; Karadag, Ayse (ELSEVIER, 2023)
The purple basil leaf extract (PBLE) was encapsulated in double emulsion (W1/O/W2)-loaded beads (emulgel) by electrospraying. The influence of & kappa;-carrageenan (& kappa;-CG) and cross-linking agents (Ca2+/K+) on the properties of alginate (SA) beads were assessed. In emulgel beads, & kappa;-CG inclusion resulted in larger sizes and more distorted shapes, wrinkles on the surface, and lower gel strength. The encapsulation efficiency of anthocyanins (ACNs) in emulgel beads ranged from 70.73 to 87.89 %, whereas it ranged from 13.50 to 20.67 % in emulsion-free (hydrogel) beads. Fourier transforms infrared (FTIR) revealed the crosslinking of SA and & kappa;-CG with Ca2+ and K+, thermogravimetric analysis (TGA), derivative thermogravimetric (DTG), and differential scanning calorim-etry (DSC) thermograms showed emulgel beads yielded higher thermal stability. The emulgel beads elevated the in vitro bioaccessibility of ACNs under simulated digestion. At the gastric phase, 86 % of ACNs in PBLE, and 46 % of loaded ACNs in hydrogel beads were released, whereas no release was occurred in emulgel beads. At the intestinal phase, after 150 min of digestion, no ACNs were detected in PBLE and hydrogel beads, whereas all emulgel beads continued to release ACNs until 300 min. The incorporation of double emulsions in hydrogel beads can be utilized in the development of functional foods.
Keywords: In vitro digestion; Release; Emulgel; Hydrogel; Extrusion; PHYSICOCHEMICAL CHARACTERIZATION; ANTIOXIDANT PROPERTIES; PHENOLIC COMPOSITION; KAPPA-CARRAGEENAN; STABILITY; OPTIMIZATION; MICROBEADS; PARTICLES; GELATIN; STORAGE; Biochemistry & Molecular Biology; Chemistry; Polymer Science